Public Finance in Theory and Practice Second edition. - Ulbrich, Holley H. (Taylor & Francis, 2011)
Public Finance in Theory and Practice is the most accessible introduction to public finance and public economics available and is any student's first stop for the key tenets of the field including public goods and externalities, taxation, provision for health and education and the analysis of government's role in the economy. With the accession to power in the United States of an administration promising to take a more active role in the economy, now is the time to take stock of how far this process should proceed. Ulbrich's book is the perfect guide to the changing world of public finance.